GUIDED PERCUTANEOUS DRAINAGE FOR INTRA-ABDOMINAL COLLECTIONS: THE FIRST CHOICE IN MODERN SURGICAL PRACTICE. (Iraqi Journal of Medical Sciences, 2016)
Background:Over the past 20 years, percutaneous drainage of intra-abdominal collections has evolved from revolutionary to routine, replacing open surgical abscess drainage in all but the most difficult or inaccessible cases.Objective:To evaluate the practical safety and efficacy of image-guided perctaneous drainage for different intra-abdominal collection.Method:Patients with intra-abdominal collections underwent percutaneous drainage under ultrasound guide were studied prospectively in Al-Imamian Al-Kadhymian Medical City over the period of 20 month from February 2011 to September 2012. The procedure done under local anesthesia and aseptic technique under ultrasound or CT scan guidance.Results:There were 50 patients (32 females and 18 males), Age ranging 12-58 years. Forty seven patients had a previous operative procedure and three patients had no such history. The post-operative collections in majority of patients 34 (72%) were single while in 13 patients (28%) were multiple. The type of content was as following: pus in 32 patients (64%), bile in 13 patients (26%), infected pancreatic/gastric secretions in 3 patients (6%) and infected urine in 2 patients (4%)., Percutaneous drainage was successful in 42 cases (84%), while 8 cases (16%) needed further surgical intervention to cure the collection. No major complications were recorded only minor complications like minor bleeding and wound infections. Mortality was in one case and it is not directly related to percutaneous drainage procedure rather to underlying problem and sepsis after second exploration.Conclusion:Guided percutaneous drainage is a safe and effective procedure for treating an intra-abdominal collections and it can be the first line treatment in severely ill patients.Key Words:Guided percutaneous drainage, abdominal collections.
Keywords: Guided percutaneous drainage; abdominal collections